A Heterogeneous Data Matching Algorithm with Combining First-Order Logic and Semantic Similarity - Gang Liu; Caixia Lu; Shaobin Huang; Suyan Sun (2014 International Conference on Information Science & Applications (ICISA), 2014)
In this paper studies a kind of information matching method based on neural network, and the method combines first-order logic and semantic similarity to complete the table matching, using SOM+ to generate feedback neural network to complete the field matching. The method can effectively reduce the matching time complexity. And by using history match, it effectively reduces the training time of neural network, improving the accuracy of matching.